2015
DOI: 10.1590/0004-282x20150022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the SLICS use in the treatment of subaxial cervical spine injuries

Abstract: The SLICS (Sub-axial Cervical Spine Injury Classification System) was proposed to help in the decision-making of sub-axial cervical spine trauma (SCST), even though the literature assessing its safety and efficacy is scarce. Method We compared a cohort series of patients surgically treated based on surgeon’s preference with patients treated based on the SLICS. Results From 2009-10, 12 patients were included. The SLICS score ranged from 2 to 9 points (mean of 5.5). Two patients had the SLICS < 4 points. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
(10 reference statements)
0
7
0
4
Order By: Relevance
“…2,[4][5][6][7]12,16,20,23 However, a classification must be practical, reliable, and valid prior to its adoption in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…2,[4][5][6][7]12,16,20,23 However, a classification must be practical, reliable, and valid prior to its adoption in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…SLICS may help surgeons with the standardization of care as well as with the choice of more unstable patterns for surgical treatment. 14 Joaquim et al, 15 in a retrospective study, demonstrated that there was more than 90% agreement between the SLIC score and treatment algorithm chosen by the surgeon. Stone et al 5 compared the interobserver and intraobserver reliability of the CSISS, the subaxial injury classification (SLIC) and severity scale, and the Allen-Ferguson (AF) system system in patients with subaxial cervical spine injuries.…”
Section: Compressionmentioning
confidence: 98%
“…Burst Distraction Translation Rotation consistency for both SLICS and CSISS was indicated by the worsening of score reflecting worse injury. da Cruz et al 14 published his results in 2015 by comparing a cohort of surgically treated patients who underwent surgery on the surgeon's preference, with those who underwent surgery based on the SLICS score. Two patients had the SLICS of less than 4 points.…”
Section: Compressionmentioning
confidence: 99%
“…Cervical facet joint dislocation is generally managed surgically. The Subaxial Injury Classification System and Severity Score (SLICS) suggests that a unilateral or bilateral facet dislocation must be managed surgically, even in the absence of SCI (Level of Evidence: III) 10,11,15 . Conservative management is associated with a high incidence of recurrent instability and long-term pain and disability (Level of Evidence: III) 16,17,18,19,20 .…”
mentioning
confidence: 99%